LOCAL CULTURAL ENCULTURATION IN THE EDUCATION OF BOTI TRIBE CHILDREN IN BOTI VILLAGE, KIE SUB-DISTRICT SOUTH CENTRAL TIMOR DISTRICT - Fransina Aprilyse Ndoen; Susilo S Utomo; Malkisedek Taneo; Andreas Ande (Jurnal Scientia, 2022)
The inheritance of local culture for Boti Dalam tribe children is carried out at home through activities and behaviors inherited by parents to children. The Boti Dalam community adheres to the Halaika belief. Dependence and obedience to nature shape the character of the Boti Dalam tribe to maintain balance with nature. This research was conducted in the Boti Dalam Tribe in Kie District, South Timor Tengan Regency. This research uses descriptive qualitative methods. Data were collected through interviews, observations and documentation studies. The results showed that the process of enculturation of local culture for children of the Boti Dalam tribe was carried out by parents to children through several stages, among others: 1) Learning about culture, the life of the Inner Boti Community is governed by applicable customs. Traditional ceremonies and rituals that are carried out teach children to know the existing taboos or prohibitions as well as sanctions if they violate these prohibitions, 2) Learning with culture, children's involvement in participating in ceremonies and rituals and the behavior shown by parents to children becomes a medium of learning for children, 3) Learning through Culture, strengthening cultural values, 4) Learning Cultured, can be seen from the attitudes possessed by children are: religious, tolerance, kinship and mutual cooperation, protecting and preserving nature. The relationship between Boti Dalam tribe children who do not go to school and Boti Luar children who go to school is very harmonious, helping each other, complementing each other, supporting each other, this good relationship can be seen in the daily activities of children.